Pain in fibrous dysplasia: relationship with anatomical and clinical features. (4th July 2019) - Majoor, Bas C J; Traunmueller, Eva; Maurer-Ertl, Werner; Appelman-Dijkstra, Natasha M; Fink, Andrea; Liegl, Bernadette; Hamdy, Neveen A T; Sander Dijkstra, P D; Leithner, Andreas
Abstract : Background and purpose — Fibrous dysplasia (FD) is a rare bone disorder associated with pain, deformities, and pathological fractures. The pathophysiological mechanism of FD-related pain remains ill-understood. We evaluated the degree of pain and the potential contributory factors in 2 patient cohorts from Austria and the Netherlands. Patients and methods — 197 patients (16–85 years) with FD (Graz n = 105, Leiden n = 92) completed a survey concerning the presence and severity of pain at their FD site. Sex, age, type of FD, and localization of FD lesions were examined for a relationship with the presence and severity of pain. Results — Of 197 patients from the combined cohort (61% female, mean age 49 (SD 16) years, 76% monostotic) who completed the questionnaires, 91 (46%) reported pain at sites of FD lesions. Severity of pain was higher in patients with lesions of the lower extremities and ribs compared with upper extremity or craniofacial lesions. Severe subtypes of FD (polyostotic/McCune–Albright syndrome) were more often associated with pain, often severe. Interpretation — Our data suggest that almost 50% of patients with FD report pain at FD sites, thus representing a major clinical manifestation of the disorder, importantly also in patients with monostotic lesions. Lesions in lower extremities and ribs were more painful.